Glut-1 explains the evolutionary advantage of the loss of endogenous vitamin C-synthesis: The electron transfer hypothesis. Issue 1 (28th August 2019) - Hornung, Tabea C; Biesalski, Hans-Konrad
Abstract: Introduction: During evolution, some species including humans, monkeys and fruit bats lost the ability for ascorbic acid (AA) biosynthesis due to inactivation of the enzyme l -gulono-lactone oxidase (GLO) and subsequently became dependent on dietary vitamin C. There are four current hypotheses in relation to the benefit of vitamin C dependence in the context of adaptation and reproduction. Here we advance and test a new 'electron transfer hypothesis', which focusses on the role of the expression of glucose transporter 1 (Glut-1) in red blood cells (RBCs) in recycling vitamin C, thereby increasing the efficiency of micronutrient uptake. Methods: To evaluate the benefit of Glut-1 expression, we determined vitamin C uptake into RBCs and potential release from two different species, humans with l -Gulono-lactone-oxidase (GLO-loss) and pigs with functional GLO. Results: The oxidized form of vitamin C (dehydroascorbate, DHA) was transported into human RBCs via Glut-1. There was no transport of either the reduced (AA) or the oxidized vitamin in pig erythrocytes. Conclusion: We propose that the transport of vitamin C increases an intracellular electron pool, which transfers electrons from intracellular ascorbate to extracellular substances like ascorbyl free radical or DHA, resulting in 100-fold smaller daily requirement of this essential redox sensitive micronutrient. This would be an advantage during seasonal changes of the availability from food and may be the key for the survival of individuals without vitamin C biosynthesis. Lay Summary: 40 million years ago some individuals lost the ability to synthesize vitamin C. Why did they survive such as humans until now? Individuals with a specific glucose transporter Glut-1 on their erythrocytes which transports vitamin C need less and are protected from scarcity due to seasons and food competitors.